The Characterization of Nanoemulsion Gel of Tobacco Leaves Extracts in Variation of Tween 80 and Sorbitol as Surfactant and Cosurfactant - Kori Yati; Gozan, Misri; Jufri, Mahdi; Wahid, Mardiastuti (Farmasains : Jurnal Farmasi dan Ilmu Kesehatan, 2026)
Research showed the potential of tobacco (Nicotiana tobacco) leaves as an antifungal. The tobacco leaves (Nicotiana tobacco) have been studied to have antifungal activity. To facilitate the use of the extract, the tobacco leaf extract was formulated into a nanoemulsion gel using Virgin Coconut Oil (VCO) as an oil phase and Tween 80: sorbitol as a surfactant and co-surfactant.  Tobacco leaves were soaked in ethanol using the maceration method, and then the liquid was taken out with a rotavapor machine. After that, the mixture was heated in a water bath (t = 85ºC) to make it thicker. Tobacco extract was identified and formulated in a nanoemulsion gel. Nanoemulsion gel was made into 3 formulas with different concentrations of Tween 80 and sorbitol. Nanoemulsion gel was evaluated for organoleptic properties, pH, viscosity, cycling test, surface tension, Transmission Electron Microscopy (TEM), and particle size. Result of evaluation of best formula showed pH 4.52, viscosity 365-573 mPa.s, surface tension 28450±0.21 N/m, morphology spherical shape, particle size 55.1±1.3 nm, polydispersity index 0.236±0.003, and zeta potential -5.16±0.35 mV (n=3). Based on the results of the research, it can be concluded that the most stable formula of tobacco leaves nanoemulsion was formula R1, with Virgin Coconut Oil (VCO) at 6% and a surfactant-to-cosurfactant ratio of 20%:10%. Statistical analysis results for all evaluations showed that all formulas have significant differences (p ≤ 0.05).